Sprint physiology and performance determinants in elite track cyclists - Dunst, A. K.; Holmberg, H.-C.; Hesse, C.; Kowalski, T.; Klich, S. (International Journal of Sports Medicine, 2026)
This study investigated the temporal dynamics of metabolic energy contributions during maximal cycling sprints lasting up to 60 seconds and explored their association with key performance metrics in elite track cyclists. Fifteen elite male track cyclists (11 sprint specialists and 4 endurance specialists) performed four maximal sprints of 3, 8, 12, and 60 seconds, as well as a cardiopulmonary exercise test. Alactic, lactic, and aerobic energy contributions were quantified based on the net energy supply methodology. Energy system contributions demonstrated clear temporal specificity: the alactic pathway dominated shorter sprints (3 s: 87±4%, 8 s: 61±5%, and 12 s: 50±6%), while the lactic pathway became the primary contributor during 60-second efforts (42±4%). Despite significant inter-individual differences in sprint performance, relative energy system contributions remained consistent across athletes. Neuromuscular performance metrics, particularly maximal power output and anaerobic power reserve, emerged as primary determinants of early sprint performance, while anaerobic work capacity became increasingly important for sustaining power output during extended efforts, underscoring the importance of both neuromuscular performance and fatigue resistance. These findings support a hierarchical but metabolically interdependent model of sprint performance, in which anaerobic power initiates performance but requires aerobic support to preserve high-intensity output under fatigue. This framework informs the design of training periodization, targeted interventions, supplementation strategies, and recovery protocols in sports requiring maximal efforts lasting up to 60 seconds.